2023
DOI: 10.1538/expanim.22-0115
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of protective effects of hesperetin and pectolinarigenin on high-fat diet-induced hyperlipidemia and hepatic steatosis in Golden Syrian hamsters

Abstract: A comparative study was conducted to determine whether hesperetin and pectolinarigenin could lower total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL), and high-density lipoprotein cholesterol (HDL) in a high-fat diet (HFD)-induced high lipid model in Golden Syrian hamsters. 48 Golden Syrian hamsters (8 weeks old) were fed with a HFD for 15 days. HFD induced significant increases in plasma TC, TG, LDL, and HDL. Then, these high lipid hamsters were divided into four groups and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Hesperidin can reduce altered redox homeostasis in experimental hyperlipidemia rat models ( Kumar et al, 2020 ). Compared with the control group, the body weight, obesity index, serum TC, TG, liver TC, TG and free fatty acid levels of hyperlipidemia hamsters treated with hesperetin were significantly decreased ( Shi et al, 2023 ). Available evidence from randomized controlled trials suggests that quercetin supplementation does not have any clinically relevant effect on plasma lipids, except for a significant reduction in triglycerides at doses above 50 mg/day ( Sahebkar, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hesperidin can reduce altered redox homeostasis in experimental hyperlipidemia rat models ( Kumar et al, 2020 ). Compared with the control group, the body weight, obesity index, serum TC, TG, liver TC, TG and free fatty acid levels of hyperlipidemia hamsters treated with hesperetin were significantly decreased ( Shi et al, 2023 ). Available evidence from randomized controlled trials suggests that quercetin supplementation does not have any clinically relevant effect on plasma lipids, except for a significant reduction in triglycerides at doses above 50 mg/day ( Sahebkar, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that 10 out of 96 flavonoids significantly inhibited OCT2. Among them, pectolinarigenin, luteolin, echinatin, chrysin, flavone, 6‐hydroxyflavone, and pinocembrin are the main active ingredients in some frequently used TCM (Cheriet et al, 2020; Fu et al, 2013; Imran et al, 2019; Naz et al, 2019; Rasul et al, 2013; Shi et al, 2022). Pectolinarigenin is mainly found in Cirsium japonicum , luteolin is the main active ingredient in Lonicera japonica , echinatin is abundant in Glycyrrhiza inflata , chrysin and pinocembrin are plentiful in Propolis, flavone is found in Ginkgo biloba L, and 6‐hydroxyflavone is extracted from Barleria prionitis Linn.…”
Section: Discussionmentioning
confidence: 99%
“…The administration dose of flavonoids was adopted from reports in the literature. The mice were pretreated by oral gavage with a single dose of 100 mg/kg for chrysin (Xu et al, 2019), biochanin A (Liu et al, 2016), 6‐methylflavone, 6‐hydroxyflavone (Din et al, 2020), and pectolinarigenin (Shi et al, 2022), whereas 200 mg/kg for luteolin (Li et al, 2022). Wedelolactone (100 mg/kg) was employed as the positive control (Wang et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we investigated the effects of compound 1 on the secretion of CHO, TG, and apoB-100 in HepG2 cells and mice. We also evaluated the inhibitory effects of nobiletin ( 2 ) [ 25 27 ], hesperidin ( 3 ) [ 28 30 ], and hesperetin ( 4 ) [ 31 , 32 ] (Fig. 1 ), the citrus-derived components with reported anti-hyperlipidemic effects, on CHO secretion in HepG2 cells and compared their mode of action with that of compound 1 .…”
Section: Introductionmentioning
confidence: 99%